Comprehensive Analysis of the Immune-Oncology Targets and Immune Infiltrates of N6-Methyladenosine-Related Long Noncoding RNA Regulators in Breast Cancer - Zhang, Xiaoqiang; Shen, Li; Cai, Ruyu; Yu, Xiafei; Yang, Junzhe; Wu, Xian; Zhu, Yanhui; Liu, Xiaoan (Frontiers in Cell and Developmental Biology, 2021)
Breast cancer (BRCA) has become the highest incidence of cancers due to its heterogeneity. To pre-dict the prognosis of BRCA patients, sensitive biomarkers deserve intensive investigation. Herein, we explored the role of N6-methylandenosine-related long non-coding RNAs (m6A-related lncRNAs) as prognostic biomarkers in BRCA patients acquired from The Cancer Genome Atlas (TCGA, n=1089) dataset and RNA sequence (RNA-seq) data (n=196). Pearson correlation analysis, univariate and multivariate Cox regression were performed to select m6A- related lncRNAs associated with progno-sis. Twelve lncRNAs were identified to construct a m6A-related lncRNA prognostic signature (m6A-LPS) in the TCGA training (n= 545) and validation (n=544) cohorts. Based on the 12 lncRNAs, risk scores were calculated. Then, patients were classified into low- and high-risk groups according to the median value of risk scores. Distinct immune cell infiltration was observed between the two groups. Patients with low-risk score had higher immune score and upregulated expressions of 4 immune-oncology targets (CTLA4, PDCD1, CD274 and CD19) than patients with high-risk score. On the contrary, the high-risk group was more correlated with overall gene mutations, Wnt/β-catenin signal-ing and JAK-STAT signaling pathways. In addition, the stratification analysis verified the ability of m6A-LPS to predict prognosis. Moreover, a nomogram (based on risk score, age, gender, stage, PAM50, T, M and N stage) was established to evaluate the overall survival (OS) of BRCA patients. Thus, m6A-LPS could serve as sensitive biomarker in predicting prognostic of BRCA patients and exert positive influence in personalized immunotherapy.